Remote patient monitoring and management in nephrology: A systematic review - Abel Mata-Lima; Ana Rita Paquete; José Javier Serrano-Olmedo (Nefrología (English Edition))
Chronic kidney disease (CKD) is a global public health problem, with adverse outcomes of kidney failure, cardiovascular disease (CVD), and premature death. According to European Kidney Health Alliance (EKHA) currently, 1 in 10 Europeans has chronic kidney disease (CKD) and it is predicted to be the fifth leading cause of death worldwide by 2040. The COVID-19, pandemic has further worsened the situation, with CKD being the number one risk factor for CKD mortality, ahead of lung and heart disease. In addition to rising mortality figures, treatments for kidney disease have not improved substantially over the past 50 years, leaving too many kidney patients with a poor quality of life and reduced life expectancy. This situation is associated with staggering aggregate annual costs amounting to €140 billion per year in Europe, more than the annual healthcare costs of cancer or diabetes.Many studies confirm that Information and Communication Technology intervention (ICT) in nephrology can be way to tackles this issue. The increased daily use of information and communication technologies (ICT) may lead to the need for healthcare professionals to monitoring patient remotely. Remote Patient Monitoring (RPM) have the potential to improve care for patients with kidney disease.RPM may provide a means to overcome some of the aforementioned barriers. RPM is a framework for monitoring patients at home by digital, wireless technology and extends the interactive contact of conventional clinical settings to include the patient's home. The hope is that these technologies would improve clinical outcomes through earlier recognition and correction of problems. Although few studies on telehealth in the dialysis population exist, studies do support its technical feasibility, which patient acceptance of this technology is very high, and that RPM may be able to improve outcomes in other co-morbid states shared by the ESKD population.According to Pan American Health Organization, CKD, also called kidney failure, describes the gradual loss of kidney function and is a worldwide public health problem, with adverse outcomes of kidney failure, CVD, and premature death.This study collects the papers concerning RPM and renal patient management using ICT intervention to analyze the results from considering the bioengineer's point of view. Our focus was on technology contribution.The aim of this study was to review and synthesize the available literature on the role of RPM in healthcare in nephrology. This systematic review was conducted to examine the content and results of publications on using RPM to improve the health care of patients with kidney disease, available to health care professionals (HCPs) and/or patients. The literature and our results confirm that in this field, RPM can allow cost reduction, improve the efficiency of healthcare resources, reduce human error, and overall improve the quality of life of kidney patients. Resumen: La enfermedad renal crónica (ERC) es un problema de salud pública global, con resultados adversos en términos de insuficiencia renal, enfermedad cardiovascular (ECV) y muerte prematura. De acuerdo con la European Kidney Health Alliance (EKHA), en la actualidad uno de cada 10 europeos padece ERC y se predice que sea la quinta causa principal de muerte a nivel mundial para 2040. La pandemia de COVID-19 ha empeorado aún más la situación, siendo la ERC el factor principal de riesgo de mortalidad, por delante de las enfermedades pulmonares y cardiacas. Además de incrementar las cifras de letalidad, los tratamientos de las nefropatías no han mejorado de manera sustancial durante los últimos 50 años, lo que ha hecho que muchos pacientes renales tengan mala calidad de vida y reducción de la expectativa de esta. Tal situación está asociada a unos costes anuales agregados sorprendentes, que ascienden a 140 billones de euros por año en Europa, cifra superior a los costes sanitarios anuales relacionados con el cáncer o la diabetes.Muchos estudios confirman que la intervención de las tecnologías de la información y la comunicación (TIC) en nefrología puede ser un modo de abordar esta cuestión. El incremento del uso diario de las TIC puede conducir a la necesidad de tratar a distancia a las personas por parte de los profesionales sanitarios. La monitorización remota del paciente (RPM) tiene el potencial de mejorar el cuidado de aquellos con enfermedad renal.La RPM puede aportar un medio de superar alguna de las barreras anteriormente citadas. Se trata de un marco para monitorizar a los pacientes en su casa mediante tecnología digital y sin cables, lo que amplía el contacto interactivo del entorno clínico convencional, incluyendo el domicilio de la persona. La esperanza es que dichas tecnologías puedan mejorar los resultados médicos mediante un reconocimiento y una corrección más tempranos de los problemas. Aunque existen pocas investigaciones sobre telesalud en la población de diálisis, los estudios respaldan su viabilidad técnica, con una aceptación muy alta de esta tecnología por parte del paciente, pudiendo mejorar la RPM los resultados de otros estados comórbidos compartidos por la población de enfermedad renal en estado terminal.De acuerdo con la Pan American Health Organization, la ERC, también denominada insuficiencia renal, describe la pérdida gradual de la función renal, y es un problema de salud pública mundial con resultados adversos en términos de fallo renal, ECV y muerte prematura.Este estudio reúne documentos relativos a RPM y el manejo del paciente renal con el empleo de una intervención de TIC para analizar sus resultados, considerando la óptica de los bioingenieros. Nosotros nos centramos en la contribución tecnológica.El objetivo fue revisar y sintetizar la literatura disponible sobre el rol de la RPM en la atención sanitaria nefrológica. Dicho análisis sistemático fue realizado para examinar el contenido y los resultados de las publicaciones sobre la cuestión, utilizando RPM para mejorar la atención sanitaria de los sujetos con enfermedad renal, disponible para profesionales sanitarios o pacientes. La literatura y nuestros hallazgos confirman que, en este campo, la RPM puede contribuir a reducir los costes, mejorar la eficiencia de los recursos sanitarios, reducir los errores humanos y mejorar en general la calidad de vida de los pacientes renales.